Effect of Pre-Treatment and KOH Concentration on The Characteristics of Rice Husk Active Charcoal - Nurhasanah, Siti; Joni Munarso, S.; Sahara Frasetia, Ratu; Mulyawanti, Ira; Fetriyuna, Fetriyuna (International Journal Labs, 2025)
Rice husk as organic waste can be used as raw material for activated charcoal. The quality of activated charcoal is influence by the ash content in the raw material, which can inhibit the development of carbon pores and the concentration of chemical compounds during chemical activation. The purpose of this study was to determine the best treatment from pre-treatment using NaOH and KOH concentrations of 10, 20, and 30% on rice husk charcoal activation to produce activated charcoal with the best morphological and proximate characteristics. The method used in this study is an experimental laboratory approach for the characterization and activation of rice husk charcoal. The results showed that the lowest water content of activated charcoal was obtained with N30 treatment, namely non-pre-treatment with activation using 30% KOH and P30 treatment (pre-treatment and 30% KOH), namely 1.23 and 1. 47%. Activated charcoal with NaOH pre-treatment all had lower ash content compared to non-pre-treated activated charcoal and commercial charcoal. The morphological characteristics showed that the development of activated charcoal pores of rice husk with pre-treatment was better than non-pre-treatment, which was indicated by the number of pores in a certain area unit. Increasing the concentration of KOH resulted in a decrease in the water content and ash content as well as an increase in the porosity of the activated charcoal of rice husk.